2017
DOI: 10.12681/jhvms.15520
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal morphograhy of broilers fed diets supplemented with perlite

Abstract: ABSTRACT. Aim of the study was to investigate effects of different levels of perlite on intestinal morphometry in broilers (Ross 308). A hundred and eighty broiler cockerels were randomly allocated into three experimental groups (3 replications and 20 broilers per pen) and fed experimental diets supplemented with different levels of perlite (0%, 2%, 4%). At 21, 28, 35 and 42 days of the study, 2 broilers were randomly selected from each replication, slaughtered and various sections of small intestine (1, 10, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…With addition of zeolite to ration, passage rate of feeds through digestive tract was decreased and nutrients were more exposed to digestive tract enzymes (Khambualia et al, 2009). Ghalehkandi et al (2014) found that different levels of perlite significantly increased average villi height in broilers. Also, the author pointed out that there would be a good relationship between section of intestine and weight gain.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…With addition of zeolite to ration, passage rate of feeds through digestive tract was decreased and nutrients were more exposed to digestive tract enzymes (Khambualia et al, 2009). Ghalehkandi et al (2014) found that different levels of perlite significantly increased average villi height in broilers. Also, the author pointed out that there would be a good relationship between section of intestine and weight gain.…”
Section: Resultsmentioning
confidence: 90%
“…The name of "perlit" is derived from the word "perle", which means pearl (Orhun, 1969). Raw perlite is transparent and greyish or gloss black rock of hydrated aluminosilicates of alkali (i.e., Na+, K+) and alkaline earth cations (Ghalehkandi et al, 2014). Perlite expands by 10-30 times its original volume when heated up to 700-1200 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Six birds were randomly selected from each replication, slaughtered and the entire gastrointestinal tract was removed. Various sections of small intestine -A, B, C, D, E and F (1, 10, 30, 50, 70 and 90%, respectively) were sampled (a 7-cm sample was taken), rinsed with phosphate buffer solution (PBS, pH=7) and stored at -80 ºC (Ghiasi Ghalehkandi et al, 2014). All experimental procedures were performed according to the Guide for the Care and Use of Laboratory Animals by the National Institutes of Health (USA) and the current laws of the Iranian government.…”
Section: Methodsmentioning
confidence: 99%